2002
DOI: 10.1590/s0100-29452002000300004
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis from zygotic embryos of Euterpe oleracea Mart.

Abstract: The aim of this work was to study the morphogenetic responses of zygotic embryos of açai palm (Euterpe oleracea Mart.) submitted to several conditions of in vitro culture. Several research experiments were conducted, in laboratory, using vegetable material collected from açai palm plants at Embrapa Amazon Oriental, Belém-PA, Brazil. It was possible to verify the expression of a direct, repetitive and no-synchronized model of somatic embryogenesis in mature zygotic embryos cultivated in primary MS medium supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 6 publications
2
11
0
9
Order By: Relevance
“…In our work the observed embryos have similar morphologies to those described previously on other melon cultivars (Kageyama et al, 1990) and other plant species (Ledo et al, 2002).…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…In our work the observed embryos have similar morphologies to those described previously on other melon cultivars (Kageyama et al, 1990) and other plant species (Ledo et al, 2002).…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…The combination between 4.44µM BAP and NAA may promote an initial stimulus for the development of embryos. Similar results were reported by LÉDO et al (2002) andLEITE et al (2014) in cultivations with Euterpe oleracea Mart. and Orbignya oleifera Burret, respectively.…”
supporting
confidence: 89%
“…Those characteristics were also noticed by Steinmacher et al (2007), when embryogenic calluses were transferred to a regeneration medium. Likewise, Ledo et al (2002) also observed an asynchrony in the development of somatic embryos in Euterpe edulis obtained from zygotic embryos cultured in the presence of 2.4-D.…”
Section: Resultsmentioning
confidence: 76%